A Força Pública de São Paulo: da profissionalização à sua intervenção no regime militar - Mussolini Filho, Luiz Sérgio (2007)
The study of professionalization of state military officer constitutes a gap in the National Political Science. In the period comprised between the coming of the French Mission, until we arrieve at the dictatorial period, that started in the year of 1964, with the military coup, we observed through the bibliografhy that some mechanisms of the State, were put in use in a very intenser manner, as to put down civil disturbs, as meetings, public demosntrations and social movements, among them we can mention the student movement. Among the mechanisms of the State, we find in the midst of the Bureau of Public Security, the Public Force, that was used to combat actions of people or groups that contested the Military Regime, actions that not rarely, generated confrontation with parto f the population, students, journalists, teachers, scinetists and even universities. However, the literature about the subject contemplates and restricts itself to the role practiced by militaries constituent of the federal sphere, setting aside, and many times even making reference, to the militaries in the state sfhere.